2001
DOI: 10.26719/2001.7.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trauma on the mental health of Palestinian children and mothers in the Gaza Strip

Abstract: A cross-sectional study was conducted among 286 Palestinian children 9-18 years of age and their mothers in the Gaza Strip. Traumatic events recollected by children living in areas of conflict, the prevalence of post-traumatic stress reactions and the relationship between children’s and mothers’ mental health were investigated. The Gaza Traumatic Events Checklist, Impact of Event Scale [IES] and General Health Questionnaire [GHQ] were used to measure outcome. Children experienced on average four traumatic even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
5
18
1
Order By: Relevance
“…In another study of 944 aged 10-19 years Palestinian children in the Gaza Strip [6] found that 32.7% of children were rated as having PTSD [7] in study of Palestinian children found that 24% of children reported PTSD. In study [8] of 349 children from Gaza Strip and West Bank found that 39.2% of children from the Gaza Strip reported post traumatic stress disorder (40 and above in IES) compare to 34% in the West Bank.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In another study of 944 aged 10-19 years Palestinian children in the Gaza Strip [6] found that 32.7% of children were rated as having PTSD [7] in study of Palestinian children found that 24% of children reported PTSD. In study [8] of 349 children from Gaza Strip and West Bank found that 39.2% of children from the Gaza Strip reported post traumatic stress disorder (40 and above in IES) compare to 34% in the West Bank.…”
Section: Introductionmentioning
confidence: 93%
“…by witnessing bombardment and shelling (83.6%). [4] In study of Palestinian mothers and children found that 34.3 % of the children fulfilled criteria of PTSD. In another comparative study of children witnessed bombardment of their homes, 59.3% of children reported PTSD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Thabet et al, 2001). These results reveal the indirect effect of political violence on child mental health through parental reactions to such violence.…”
mentioning
confidence: 94%
“…A. Thabet, Abed, and Vostanis (2001) devised the Gaza Traumatic Events Checklist to establish the nature of traumatic events experienced by Palestinians. They found that in a sample of 286 children, 92% reported watching mutilated bodies of Palestinians on TV and 84% reported witnessing bombardment to people and houses.…”
mentioning
confidence: 99%